PRAANGGAPAN PEMERAN FILM LAYANGAN PUTUS KARYA BENNI SETIAWAN - Hasni Hasni; Akmal Hamsa; Aswati Asri (Fakultas Teknik Universitas Negeri Makassar, 2023)
This research is a qualitative research with the aim of describing the types and meanings of presuppositions contained in the actors of the demands in the film Layangan Putus by Benni Setiawan. The research data is the story of the actors in the film Kite Disconnect. The source of the data in this study was the film Layangan Disconnect which was downloaded via the WeTV application. Data collection techniques are document techniques, observation, listening, and note taking. The results of the study show that the types and meanings of the presuppositions contained in the speech in the film Layangan Putus by Benni Setiawan are factual presuppositions stating the meaning of real information or a fact, non-active presuppositions stating meanings that are not true or unreal, counterfactual presuppositions stating the meaning of something that is wrong and contrary to reality, Existential presuppositions state the meaning of identity existence, structural presuppositions state the use of question words to state information that is considered true, and lexical presuppositions state implied or different meanings from what is said. dominant lexical presuppositions were found, while few counterfactual presuppositions.